Phase space analysis of inclusive charged current proton production in MicroBooNE - Alrashed, Munerah (Kansas State University, 2019)
Using the full five-dimensional phase space, measuring the relative fraction of ν[subscript μ] charged current events containing a proton in the final state originates from quasielastic, 2p2h, resonance, and deep inelastic sub-nuclear scattering processes within the context of the GENIE cross section model. These studies indicate that the data support the picture that charged current scattering is dominated by a relatively small number of incoherent nucleon-level processes. GENIE successfully predicts, within the estimated experimental uncertainties, the relative contributions of each subnuclear process. This analysis of MicroBooNE data establishes the presence of a 2p2h contribution to the cross section to a significance of 7.3 σ.
Keywords: Phase space analysis